Assessing the Knowledge and Attitudes of Eligible Couples Regarding Small Family Norm in a Selected Rural Area of Gwalior - Madan Dara; Mini Anil; Rakesh Kumar (International Journal of Community Health Nursing And Practices, 2023)
This study aimed to determine the level of knowledge and attitude of eligible couples toward permanent family planning methods in a selected rural area of the district. The research method was an evaluation. Sixty couples were chosen at random who met the inclusion and exclusion criteria. The primary purpose of this research is to evaluate the level of understanding and satisfaction with permanent family planning methods among eligible couples in rural areas. In this investigation, random sampling was used. The Health Belief Model developed by Rosenstock serves as the theoretical foundation for this investigation. The Health Belief Model was created to offer an explanation for why some people take precautions to safeguard their families' health while others do not. Considering the research objectives, the data was analyzed in alignment with the study's aims. Collectively, we looked at the data via the lenses of frequency, mean, and mean percentage. Data from the Linkert attitude scale, a questionnaire on permanent family planning methods, and sociodemographic can all be used to evaluate the effectiveness of the tool description. Within the same group, comparisons were conducted using statistical methods such as one-way analysis of variance and unpaired t-test. In this analysis, we employed an unpaired t-test for categorical variables.
Keywords: Knowledge and attitude; eligible couples; permanent family planning methods